Comparison of cycloplegic refraction in children with different iris colour categories. A cross- sectional survey - Aisha Arooj; Qazi Muhammad Omair; Shazia Bano (Journal of the Pakistan Medical Association)
Objective: To compare the cycloplegic refraction in children with different iris colour categories and age groups.